Land system change - Karen Morrow (Research Handbook on Law, Governance and Planetary Boundaries, 2021)
The land system change planetary boundary applies to the conversion of land from its natural state for human purposes. It is significant in its own right and also in interacting with many of the other planetary boundaries. As distinct from purely hard science boundaries, land use change is visibly rooted in societal ordering and raises not only quantitative but also qualitative, functional, and spatial issues. Thus addressing this boundary is particularly challenging, not least in selecting an appropriate indicator to represent it. This is evident in the current chosen indicator, global forest area, which is politically and legally contentious, illustrating the considerable challenges in mapping the science of planetary boundaries to human social systems.